Nuclear dynamics in the nucleonic regime - Durand, Dominique. (Taylor & Francis, 2011)
Over the last decade one of the most active areas of research in nuclear physics has been the study of systems of nucleons in various dynamical situations. Heavy-ion collisions at beam energies in the range 30-150 MeV per nucleon, where subnucleaonic degrees of freedom can be considered as frozen, allow such systems to be studied in detail. Nuclear Dynamics in the Nucleonic Regime summarizes our current understanding of this branch of physics. The authors follow the course of typical heavy-ion collisions through time and discuss each stage of the collisions. By presenting experimental and theoretical understanding, a clear picture of the physics can be presented.